Gelatin-/Alginate-Based Hydrogel Scaffolds Reinforced with TiO2 Nanoparticles for Simultaneous Release of Allantoin, Caffeic Acid, and Quercetin as Multi-Target Wound Therapy Platform - Marija M. Babić Radić; Marija Vukomanović; Jasmina Nikodinović-Runić; Simonida Tomić (MDPI AG, 2024)
This study proposes synthesis and evaluation of gelatin-/alginate-based hydrogel scaffolds reinforced with titanium dioxide (TiO2) nanoparticles which, through their combination with allantoin, quercetin, and caffeic acid, provide multi-target therapy directed on all phases of the wound healing process. These scaffolds provide the simultaneous release of bioactive agents and concurrently support cell/tissue repair through the replicated structure of a native extracellular matrix. The hydrogel scaffolds were synthesized via a crosslinking reaction using EDC as a crosslinker for gelatin. Synthesized hydrogel scaffolds and the effect of TiO2 on their properties were characterized by structural, mechanical, morphological, and swelling properties, and the porosity, wettability, adhesion to skin tissue, and simultaneous release features. The biocompatibility of the scaffolds was tested in vitro on fibroblasts (MRC5 cells) and in vivo (Caenorhabditis elegans) in a survival probe. The scaffolds revealed porous interconnected morphology, porosity of 88.33 to 96.76%, elastic modulus of 1.53 to 4.29 MPa, full hydrophilicity, favorable skin adhesivity, and biocompatibility. The simultaneous release was investigated in vitro indicating dependence on the scaffold's composition and type of bioactive agents. The novel scaffolds designed as multi-target therapy have significant promise for improved wound healing in a beneficial and non-invasive manner.